Peculiarities of the Purification the Gaseous Mixtures Containing Bromine Fluorides Using Solid Absorbers; First International Siberian Workshop ISIF-2003 on Advanced Inorganic Fluorides (INTERSIBFLUORINE-2003), Novosibirsk, 2-4 April 2003 - Amelina G. N. Galina Nikolayevna; Gordienko V. V.; Zherin (Gerin) I. I. Ivan Ignatyevich; Zhiganova A. A.; Rudnikov A. I.; Torgunakov Yu. B. (2003, 2003)
В фонде НТБ ТПУ отсутствует